1989
DOI: 10.1093/jn/119.8.1223
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Locomotor Activity of Rats Made Histidinemic by Injection of Histidine

Abstract: Acute histidinemia was provoked in 30-d-old male Wistar rats by injecting intraperitoneally either histidine alone (0.5 mg/g body wt) or histidine (0.25 mg/g body wt) plus the histidase inhibitor nitromethane (0.73 mg/g body wt). Histidase activity was approximately 90% inhibited in rats receiving nitromethane. Serum histidine in both groups reached levels similar to those of histidinemic patients. Rats were subjected to the open field behavioral task, and the number of rearings and crossings were counted. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the pathomechanisms involved in the brain injury in these patients are yet not established. In this context, we have previously demonstrated that histidine administration provokes learning deficits in rats (Dutra-Filho et al, 1989), suggesting that the amino acid probably provokes alterations in the brain leading to cognitive deficit. Table 2 In vitro effect of l-␤-imidazolelactic acid on antioxidant enzyme activities in cerebral cortex homogenates from young rats l-␤-Imidazolelactic acid concentration (mM) Since oxidative stress is involved in the neuropathology of various neurodegenerative disorders, including Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis, and others (Halliwell, 2001) and considering that pro-oxidant properties have been demonstrated for histidine in various tissues but not in brain, in the present study we investigated the role of l-histidine on various parameters of oxidative stress in cerebral cortex of young rats.…”
Section: Discussionmentioning
confidence: 96%
“…However, the pathomechanisms involved in the brain injury in these patients are yet not established. In this context, we have previously demonstrated that histidine administration provokes learning deficits in rats (Dutra-Filho et al, 1989), suggesting that the amino acid probably provokes alterations in the brain leading to cognitive deficit. Table 2 In vitro effect of l-␤-imidazolelactic acid on antioxidant enzyme activities in cerebral cortex homogenates from young rats l-␤-Imidazolelactic acid concentration (mM) Since oxidative stress is involved in the neuropathology of various neurodegenerative disorders, including Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis, and others (Halliwell, 2001) and considering that pro-oxidant properties have been demonstrated for histidine in various tissues but not in brain, in the present study we investigated the role of l-histidine on various parameters of oxidative stress in cerebral cortex of young rats.…”
Section: Discussionmentioning
confidence: 96%
“…They were maintained since birth on a 200 g protein/kg laboratory chow (Germani, Porto Alegre, RS, Brazil; for details see Dutra-Filho et al 1989).…”
Section: General Proceduresmentioning
confidence: 99%